Psychiatrist-led hepatitis C (HCV) treatment at an opioid agonist treatment clinic in Stockholm– a model to enhance the HCV continuum of care - Per-Erik Klasa; Mikael Sandell; Soo Aleman; Martin Kåberg (BMC Psychiatry)
Abstract Background People with opioid agonist therapy (OAT) represent a population with an increased hepatitis C (HCV) prevalence. Recent studies provide strong evidence regarding effective HCV treatment outcomes and low levels of reinfection in this population. Increased access to HCV care for people with OAT is essential to reach the WHO goal of eliminating HCV as a major public health threat by 2030. Methods The Maria OAT clinic, located in central Stockholm, provides OAT for approximately 500 patients. The majority have a history of injection drug use. In October 2017, psychiatrist-led HCV treatment was initiated, with remote consultation support from the local infectious diseases clinic. All OAT staff participated in HCV-specific education to increase HCV awareness. To evaluate HCV treatment outcomes for this model of care, we examined sustained virological response (SVR) and reinfection rates between January 2018 and December 2022. Results Between October 2017 and June 2022, 133 participants received HCV treatment through weekly administrations or directly observed treatment. 72% were men, and the overall mean age was 44.7 years. Six participants were retreated, giving a total of 139 treatment initiations. All were HCV RNA negative at end of treatment, and 88% reached SVR. A total of 11 reinfections post SVR were noted, with a reinfection rate of 7.3/100 person-years (95% CI 4.1–12.9). Conclusion Overall, successful HCV treatment results and levels of reinfections consistent with the literature were achieved. Bringing HCV diagnostics and treatment to an OAT clinic constitutes a good example of enhancing the HCV continuum of care. Furthermore, HCV treatment education for psychiatrists, addiction specialists and staff at OAT clinics makes HCV care more sustainable, as specifically noted during the COVID-19 pandemic. This successful model of care, introducing HCV treatment by psychiatrists on-site at OAT clinics, has now been further implemented at other OAT clinics in Stockholm.